EU ETS impact on Eco-Innovation in European countries and its influence on companies performance in Portugal: a sector analysis - Silva, Pablo Júnior Fraga da (2023)
The main goal of this study is to evaluate the influence of the European Union Emissions Trading System (EU ETS) on companies' Eco-Innovation (EI) activities, and in the Financial Performance of Portuguese firms, to evaluate its effectiveness in changing firms environmental behavior. Empirically, it intends to test whether EU ETS and its "strictness" are significantly related to EI while considering internal and external factors that may be related to EI, and also how the Portuguese companies are financially impacted by the system and its allowances market. To this end, it was developed, for the first part of the study a cross-sectional framework using the Community Innovation Survey (CIS) data and were created stringency indicators for the period 2012-2014 for 13 European countries. For the second part of the study, it was estimated a panel model with random effects for the period between 2012-2020 for Portuguese companies using European Commission's and SABI´s (Sistema de Análise de Balanços Ibéricos) database. It was found that Eco-innovation is related to internal factors, like firm size, which has a significant and negative impact on the dependent variable, and the turnover growth coefficient, which takes companies with a higher TG value to eco-innovate less, and external factors, such as the existence of environmental regulation and financial incentive that has been shown to positively impact the reduction of energy use or CO2 footprint within the company and during the consumption or use of a good or service by the end-user and for example, taxes, charges, environmental fees and EU ETS stringency that proved not to be an incentive for EI. It was also possible to observe that the impact of EU ETS is limited and there are some controversies and that the EU ETS negatively impacts the profitability of companies, as it tends to reduce emissions, and these are positively related. In addition, technology policy has become an important part of the policy portfolio that complements climate policy. Based on the findings, it is advised policy makers on how to improve the existing policy portfolio.